Evaluation of Wheat Germplasm Against Salinity - Begum, Farida; Saifuzzaman, M; Sultana, W (Bangladesh Journal of Scientific and Industrial Research, 2008)
Fifteen wheat lines/ varieties were tested under artificial saline environment in the year 2006-07 for the study of salt tolerance. Four salinity gradients, 0.38, 3.76, 8.8 and 12.0 dS-m were used. Seedling emergence, plant height and crop yield were found to be affected by salinity gradient. The varieties/lines Gaurav, Shatabdi, Sufi, Bijoy. CB-38, CB-60 and CB-78 showed better performance as evaluated on the basis of plant height, yield and yield components. These lines can thus be selected for further investigation in the coastal saline areas. The decrease in growth as attributed to the accumulation of salinity induced increase in Na+ and decrease in K+ content. This decrease in growth ultimately caused a decrease in yield. Key words : Wheat, Salinity, Crop yield, Na+, K+ content. DOI: 10.3329/bjsir.v43i2.966 Bangladesh J. Sci. Ind. Res. 43(2), 223-234, 2008